Cleisostoma hainanense, a new species (Orchidaceae: Epidendroideae) from Hainan, China: evidence from morphological and DNA analyses - Huang, Ming-Zhong; Liu, Ding-Kun; Yin, Jun-Mei; Yang, Guang-Sui (Phytotaxa, 2020)
A new species, Cleisostoma hainanense (Orchidaceae: Epidedroideae: Aeridinae) from Hainan, China, is described and illustrated. Detailed morphological comparisons indicate that C. hainanense is similar to C. paniculatum, but differs in tauren-shaped mid-lobe with truncated tip, conical spur with inconspicuous septum and arch-shaped back wall callus. The molecular study based on nuclear ribosomal ITS and four plastid (atpI-atpH, matK, psbA-trnH, rbcL) regions support that the new species is sister to C. paniculatum.